Confusion and information triggered by photos in persona profiles. Issue 129 (September 2019) - Salminen, Joni; Jung, Soon-gyo; An, Jisun; Kwak, Haewoon; Nielsen, Lene; Jansen, Bernard J.
Highlights: More contextual photos provide significantly more information to the end users concerning the persona. Showing photos of multiple people engenders confusion and lowers informativeness. Various interpretations of the persona based on the choice of photos are biased by the end users' experiences and preconceptions. Adding contextual photos increases the perceived informativeness of the persona profile with no increase in perceived confusion. Persona creators should consider the design power of photos when creating persona profiles. Abstract: We investigate whether additional photos beyond a single headshot makes a persona profile more informative without confusing the end user. We conduct an eye-tracking experiment and qualitative interviews with digital content creators after varying the persona in photos via a single headshot, a headshot and photo of the persona in different contexts, and a headshot with photos of different people with key persona attributes the gender and age. Findings show that contextual photos provide significantly more persona information to end users; however, showing photos of multiple people engenders confusion and lowers informativeness. Also, as anticipated, viewing additional photos requires more cognitive focus, which is measured by eye-tracking metrics; these metrics are correlated with levels of informativeness and confusion. Furthermore, various interpretations of the persona based on the choice of photos are biased by the end users' experiences and preconceptions. Concerning persona design, findings indicate that persona creators need to consider the intended persona use objectives when selecting photos and when producing persona profiles. Using contextual photos can improve informativeness, but this demands more cognitive focus from end users. Thus, adding contextual photos increases the perceived informativeness of the persona profile without being obfuscating, but multiple photos of different people do evoke confusion about the targeted persona.